Dinamika kehidupan ekonomi dan sosial di mekah pra islam - zaharuddin, khoirunnisa (Maliki Interdisciplinary Journal, 2025)
Our culture today is greatly influenced by pre-Islamic Arab history, especially in Mecca and other Hijaz cities. Understanding the social, economic, and cultural facets of that era is crucial since it provides a picture of Jahiliyyah society’s way of life. The dynamics of their life are reflected in their trade endeavors, literary works, and social relationships. The pre-Islamic period, which is known as the age of jahiliyyah, was marked by a lack of morals. According to the Social Construction hypothesis, the circumstances, environment, and natural resources that were available all had an impact on the development of this state. The term "jahiliyah," which refers to Arab culture prior to the coming of Islam, precisely highlights their meaningful way of life, which includes beliefs, practices, and traditions Because every event in the world cannot be isolated from the socio-historical framework that surrounds it, it is crucial to look at the sequence of events in Arab society prior to the arrival of Islam. Thus, the goal of this study is to deepen our knowledge of Arab life before to Islam as well as their economic and social history throughout that time.